A little bit about sphingolipidoses in cardiology: a clinical case of Fabry disease - Artyom A. Vedernikov; Evgeny M. Mezhonov; Nikita E. Shirokov; Alexandra M. Adamchuk; Valentina A. Balina; Oleg M. Reitblat; Valentina I. Larionova; Sergey V. Shalaev (Терапевтический архив)
The article presents a clinical case of Fabry disease in a woman, characterized by multisystemic lesions, late onset and predominant clinical picture of heart failure. The features of this pathology are described in detail with an emphasis on instrumental studies of the cardiovascular system, and the progressive course of Fabry disease is analyzed. This clinical observation illustrates the importance of family screening and detailed anamnesis, shows the process of supervision of a patient with an orphan disease by a cardiologist of a regional hospital in real clinical practice, thereby increasing awareness of the Russian medical community about this pathology.